Robotic Cholecystectomy and Common Bile Duct Exploration: Multidisciplinary Approach in a Complex Case of Choledocholithiasis - Cataldo De Palma; Antonella Delvecchio; Miriam Varvara; Francesca D’Errico; Francesco Decembrino; Giuseppe Di Giovanni; Riccardo Inchingolo; Riccardo Memeo; Michele Tedeschi (Journal of Clinical Medicine, 2026)
Introduction: Common bile duct (CBD) exploration is indicated in symptomatic patients with choledocholithiasis when endoscopic retrograde cholangiopancreatography (ERCP) is not feasible or has failed. In selected complex cases, robotic surgery may offer technical advantages over conventional laparoscopy. Material and Methods: A 51-year-old woman presented with biliary colic and ultrasound evidence of choledocholithiasis. Past medical history included congenital pyloric stenosis treated with open gastrojejunostomy at the age of 3 days, precluding ERCP. Magnetic resonance cholangiopancreatography (MRCP) and percutaneous transhepatic cholangiography (PTC) demonstrated multiple large distal CBD stones. Interventional radiology attempts failed to achieve complete clearance, and a percutaneous biliary drain was placed. The patient underwent robotic-assisted cholecystectomy and CBD exploration. Results: Following extensive adhesiolysis, robotic cholecystectomy was completed. A longitudinal choledochotomy enabled extraction of multiple stones using the chopstick technique, a Fogarty catheter, and choledochoscopic basket retrieval. After unsuccessful conventional retrieval attempts, an impacted stone was removed using a choledochoscopy-guided robotic intraductal grasping maneuver, with an 8-mm wristed forceps introduced through the choledochotomy and used exclusively for mechanical grasping. The choledochotomy was closed with continuous suturing, and intraoperative cholangiography confirmed unobstructed biliary flow without residual stones. The postoperative course was uneventful, and the patient was discharged on postoperative day seven. At two-month follow-up, cholangiography through the transcystic catheter confirmed persistent ductal clearance, allowing for catheter removal. Conclusions: This case demonstrates the feasibility of robotic CBD exploration in a selected patient with complex choledocholithiasis and altered anatomy when conventional treatment options were not feasible or unsuccessful.